Osobliwe słownictwo szesnastowiecznych leksykonów (na wybranych przykładach nazw rzemieślników) - Migdał, Jolanta (Slavia Occidentalis, 2017)
The article presents names of craftsmen which existed in the 16th century Polish language, confirmed exclusively in lexicographic collections of the time. The material has been drawn from the published volumes of Słownik polszczyzny XVI wieku (Dictionary of 16th century Polish language). A review was conducted of the way in which these peculiar names of craftsmen functioned in the lexicons, both reflecting vocabulary confirmed in Old Polish and in contemporary dictionaries. It turned out that even though some of these words were perhaps the original products of the 16th lexicographers’ imaginations, others were actually used in the vocabulary of those times.